2022
DOI: 10.3390/pathogens11091063
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Commensal Bacteria Increase Protection against Hypermucoviscous Carbapenem-Resistant Klebsiella pneumoniae ST25 Infection

Abstract: In a previous work, we demonstrated that nasally administered Corynebacterium pseudodiphtheriticum 090104 beneficially modulated the respiratory innate immune response and improved the protection against Respiratory Syncytial Virus and Streptococcus pneumoniae in mice. In this work, we aimed to evaluate whether the immunomodulatory 090104 strain was able to enhance the resistance against the respiratory infection induced by hypermucoviscous carbapenemase-producing (KPC-2) Klebsiella pneumoniae strains belongin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Corynebacterium pseudodiphtheriticum is a commensal bacterium normally found in the human nasopharynx mucosa [ 3 , 4 ]. We demonstrated that the nasal administration of viable C. pseudodiphtheriticum 090104 to mice has a remarkable capacity to beneficially modulate the respiratory immune system, increasing the resistance to respiratory syncytial virus [ 5 ], Streptococcus pneumoniae [ 6 ], and hypermucoviscous carbapenemase-producing Klebsiella pneumoniae [ 7 ]. The protective effect of the 090104 strain against the different respiratory pathogens was related to its capacity to modulate the respiratory innate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Corynebacterium pseudodiphtheriticum is a commensal bacterium normally found in the human nasopharynx mucosa [ 3 , 4 ]. We demonstrated that the nasal administration of viable C. pseudodiphtheriticum 090104 to mice has a remarkable capacity to beneficially modulate the respiratory immune system, increasing the resistance to respiratory syncytial virus [ 5 ], Streptococcus pneumoniae [ 6 ], and hypermucoviscous carbapenemase-producing Klebsiella pneumoniae [ 7 ]. The protective effect of the 090104 strain against the different respiratory pathogens was related to its capacity to modulate the respiratory innate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…In our prior investigations, we demonstrated that nasal priming with Cp 090104 or CP-derived BLPs influences the respiratory innate immune response [10][11][12]. This prompted us to examine whether this respiratory commensal bacterium's innate immune modulation extends to adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that C. pseudodiphtheriticum strain 090104 (Cp 090104) i.n. administered to mice enhanced the resistance to respiratory syncytial virus (RSV) [10], S. pneumoniae [11], and Klebsiella pneumoniae [12]. The protective ability of the Cp 090104 strain against the different pathogenic microorganisms was associated to its capacity to regulate the innate immune responses in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have used mice as a model to characterize respiratory infections caused by multiresistant K. pneumoniae isolates from the ST25 considering that among the KPC-2-producing strains, this sequence type has emerged as a persistent and overrepresented cause of hospital-associated infections in the Northwest of Argentina [ 5 , 6 , 7 ]. We demonstrated that K. pneumoniae ST25 strains were able to infect the respiratory tract of adult immunocompetent mice after the nasal challenge, inducing a potent innate immune response characterized by the increase in inflammatory cytokines and chemokines and the recruitment of inflammatory cells into the lung [ 23 , 24 ]. In fact, our previous and present results demonstrated that the nasal challenge of mice with the ST25 K. pneumoniae strains LABACER 01 and LABACER 27 increased the levels of TNF-α, IL-1β, IL-6, IFN-γ, IL-17, KC and MPC-1 in the respiratory tract and blood, as well as the numbers of BAL neutrophils and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Mice in the control group were administered only 100 µL from PBS. The infective dose selected for this work was determined previously [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%